2016
DOI: 10.1161/circresaha.115.307540
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analyses of Human Cell-Based Cardiac Regeneration Therapies

Abstract: Controversies from basic science, discrepancies from clinical trials, and divergent results from meta-analyses have recently arisen in the field of cell therapies for cardiovascular repair and regeneration. Noticeably, there are almost as many systematic reviews and meta-analyses published as there are well-conducted clinical studies. But how do we disentangle the confusion they have raised? This article addresses why results obtained from systematic reviews and meta-analyses of human cell-based cardiac regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…This was the theme of 2 very recent reviews published by well-known experts in the field[55,56]. As one would expect, the first variation factor to point the finger to is related to differences in the methodology used in conducting systematic reviews.…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This was the theme of 2 very recent reviews published by well-known experts in the field[55,56]. As one would expect, the first variation factor to point the finger to is related to differences in the methodology used in conducting systematic reviews.…”
Section: Meta-analysismentioning
confidence: 99%
“…Although ACCRUE (Meta-Analysis of Cell-Based Cardiac Studies; NCT01098591) database comprised a pool of 1252 IPDs from 12 randomized studies in AMI settings, it included only about 60% of the available published trials, as a result raising concern for potential bias. Of course, there are some other disparity factors involved, such as insufficient power of included studies, patients’ heterogeneity and statistical heterogeneity[55,56]. …”
Section: Meta-analysismentioning
confidence: 99%
“…Cell therapy of coronary artery disease has evolved rapidly from bench to bedside; however, despite positive results in murine models of MI, small‐ or medium‐sized clinical studies and meta‐analyses have only shown modest benefit in humans 4, 5, 6, 7. This could be principally because of the use of inappropriate and ill‐defined cell populations, which calls for a continued search for optimal, quality‐assured cell products.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies with skeletal myoblasts, bone marrow-derived cells, mesenchymal stem cells (MSCs) and cardiac stem cells (CSCs) have shown feasibility and initial evidence of efficacy ( Assmus et al, 2002 , de Jong et al, 2014 , Hare et al, 2009 , Menasche et al, 2008 , Sant'anna et al, 2010 ). After multiple systematic reviews and meta-analyses, the consensus is that transplantation of adult bone marrow cells modestly improves ventricular function, infarct size, and remodeling in patients with CHD compared with standard therapy, and these benefits persist during long-term follow-up ( Martin-Rendon, 2016 ). Bone marrow cell transplantation also reduces the incidence of death, recurrent MI, and stent thrombosis in patients with CHD ( Jeevanantham et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%